PSYCHOLOGICAL-PEDAGOGICAL STAGES OF SOCIAL ADAPTATION OF A PERSON (American Journal of Pedagogical and Educational Research, 2026)
This article covers the factors of the psychological and pedagogical aspects of the social adaptation of the individual and what to pay attention to on the way to increasing their accessibility to communication and the specific characteristics of the child.